The Development of Dendritic Gd-DTPA Complexes for MRI Contrast Agents - Yu, Gang; Yamashita, Mitsuji; Tian, Mei; Zhang, Hong; Ozaki, Nobuhisa; Yamashita, Junko; Fujie, Michio; Takehar, Yasuo; Sakahara, Harumi (Current Medical Imaging, 2010)
Magnetic resonance imaging (MRI) is a non-invasive and high resolution imaging technique and becomes a powerful diagnostic tool in the clinic. With the applications of MRI becoming more and more dependent on contrast agents, it is particularly important to develop efficient contrast agents. This article describes how to design an efficient dendritic Gd-DTPA complex for MRI contrast agents.
Keywords: Gd-DTPA